Armenian Conceptions of the Most Victorious Weapon and Contemporary Khachkar Culture of Artsakh - Safaryan, Anush (History and Culture, 2023)
From its first steps, the Christian ideology interpreted the Crucifixion first of all as a victory over death. In many medieval canonical and paracanonical stories and pictorial fictions, the cross is presented as the most victorious weapon. Christ thereby destroys hell, slays the dragon, conquers death, overcomes sin, etc. He is followed by various saints armed with cross-spears.  All this found its pictorial and especially scriptural expression in Khachkar culture. However, the medieval masters, characterizing the cross as a weapon or symbol of victory in the khachkar inscriptions, avoided making the cross look like a weapon or a sword in the khachkar composition.After the Artsakh Liberation War, the idea of the cross as the most victorious weapon became relevant again. A new type of monuments were created, which iconographically simply represent the cross as a weapon or a sword, combining it with a shield and other military attributes. The most unique manifestation, which is fundamentally related to the liberation struggle of Artsakh, is the unique and new phenomenon in the khachkar culture: the khachkars called "sword-cross" or "border cross", which act as guardian-symbols.
Keywords: Artsakh; khachkar culture; iconography; sign of victory; war; sword